Zeta Potential Measurements on Solid Surfaces for in Vitro Biomaterials Testing: Surface Charge, Reactivity Upon Contact With Fluids and Protein Absorption - Ferraris, Sara; Cazzola, Martina; Peretti, Veronica; Stella, Barbara; Spriano, Silvia (Frontiers in Bioengineering and Biotechnology, 2018)
Surface properties of biomaterials (e.g. roughness, chemical composition, charge, wettability and hydroxylation degree) are key features to understand and control the complex interface phenomena that happens upon contact with physiological fluids. Numerous physico-chemical techniques can be used in order to investigate in depth these crucial material features. Among them, zeta potential measurements are widely used for the characterization of colloidal suspensions, but actually poorly explored in the study of solid surfaces, even if they can give significant information about surface charge in function of pH and indirectly about surface functional groups and reactivity. The aim of the present research is application of zeta potential measurements of solid surfaces for the in vitro testing of biomaterials. In particular, bare and surface modified Ti6Al4V samples have been compared in order to evaluate their isoelectric points (IEPs), surface charge at physiological pH, in vitro bioactivity (in simulated body fluid - SBF) and protein absorption. Zeta potential titration was demonstrated as a suitable technique for the surface characterization of surface treated Ti6Al4V substrates. Significant shift of the isoelectric point was recorded after a chemical surface treatment (because of the exposition of hydroxyl groups), SBF soaking (because of apatite precipitation IEP moves close to apatite one) and protein absorption (IEP moves close to protein ones). Moreover, the shape of the curve gives information about exposed functional groups (e.g. a plateau in the basic range appears due to the exposition of acidic OH groups and in the acidic range due to exposition of basic NH2 groups).